2018
DOI: 10.3768/rtipress.2018.pb.0019.1809
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Sector Outcomes: Making the Connections

Abstract: A critical issue in international development is how donor-funded programs can support sustainable and long-lasting changes in assisted countries. Among the factors associated with sustainability is improved governance. However, many donor-funded initiatives are focused on achieving results in specific sectors, such as health, education, and agriculture. How can how governance interventions contribute to achieving sector-specific results? This brief explores this question and discusses how international develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For instance, recent research highlights that more than one third of recorded attacks on human rights defenders in 2020 stemmed from failures to consult, or obtain the FPIC of, communities. 106 This risk illustrates the need to avoid relying on "decontextualized 'best practices'" 107 and to instead design and adapt transparency interventions to the relevant context.…”
Section: Risks To Community Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, recent research highlights that more than one third of recorded attacks on human rights defenders in 2020 stemmed from failures to consult, or obtain the FPIC of, communities. 106 This risk illustrates the need to avoid relying on "decontextualized 'best practices'" 107 and to instead design and adapt transparency interventions to the relevant context.…”
Section: Risks To Community Membersmentioning
confidence: 99%
“…These strategies and approaches need to be adjusted to-and their appropriateness will depend on-the local context, 178 taking into consideration potential risks to community members and their lands (see Part IV, above).…”
Section: Responding To the Challenges: Strategies To Advance More Effective Land Investmentmentioning
confidence: 99%
“…In its broadest theoretical conceptualization, governance refers to all processes of social organization and social coordination, encompassing non‐state actors and institutions as well as government (Bevir, ). Research on governance revealed the contribution of such processes to a range of outcomes and supported increased investments specifically designed to improve governance and inclusion of governance interventions in sector programs (Brinkerhoff & Wetterberg, ). However, confusion has persisted in response to the wide variety of governance definitions, models, and prescriptions, which offer few reliable guideposts for practitioners.…”
Section: Evolution Of the Stewardship Conceptmentioning
confidence: 99%
“…In an earlier analysis of integrated governance, our starting point for examining integration was sector projects and experts whose experiences with disappointing sector results led them to integrate governance components into their interventions. 2 For this study, however, we began from the perspective of governance projects and specialists that seek to contribute to sector outcomes. We recognize that many international development funders work in integrated governance.…”
mentioning
confidence: 99%